Pengaruh Pengetahuan Keuangan, Perilaku Keuangan dan Pendapatan Terhadap Keputusan Berinvestasi Mahasiswa Kota Batam - Susanti, Susanti; Tipa, Handra (Owner : Riset dan Jurnal Akuntansi, 2024)
Along with changing times, especially improvements in the economic sector, Batam students need money as a complementary to meet their daily needs. One way to make money is investing. Students need financial knowledge as a basis for making decisions, applying appropriate financial behavior in managing their finances and adjusting income on the investment products they choose. This research has many objectives to be analyzed again, one of which is to see whether the results of this research can bring benefits to Batam City students in increasing their awareness of carrying out investment activities. The aim of this research is to find out whether financial knowledge, financial behavior and income influence the investment decisions of Batam students. The sample in this research was Batam students who took the Accounting study program, totaling 105 respondents. The method used to collect data was by form of distributing questionnaires to universities in Batam. The data analysis methods used are descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression analysis, hypothesis testing, coefficient of determination and the data is processed with help of statistical tools with SPSS version 26. The results of this study show that financial knowledge hasn’t effect on investment decisions of Batam City students. Financial behavior has a significant influence on investment decisions of Batam City students. Income has a significant influence on investment decisions of Batam City students. Simultaneously financial knowledge, financial behavior and income have a significant influence on investment decisions of Batam City students. The conclusions in this research are that H1 is rejected, H2 is accepted, H3 is accepted, and H4 is accepted